The Impact of Tourism and Research Activity on Ape Health - Sugnaseelan, Sumita; Ancrenaz, Marc; Bitariho, Robert (Cambridge University Press, 2024)
Apes have fascinated humans since antiquity: several ancient myths and legends mention their existence (Russon, 2004). Over time, scientists, philosophers and others have made comparisons between humans and apes in efforts to define precisely what characterizes “humans” and what is unique about “humanity.” Such investigations spurred research into ape behavior, communication, tool use, self-awareness, social structure, culture and social learning. As behavioral and ecological research was made available to the public, people’s fascination with the apes grew, stimulating the desire to see them in captivity and in the wild. In 1925, Parc Albert (renamed Virunga National Park in 1969), the first national park in Africa, was created to protect mountain gorillas (Gorilla beringei beringei) (Virunga National Park, n.d.-a). With the growth of the leisure industry, ex-situ and in-situ tourism operators have increasingly sought to capitalize on the fascination with apes
Keywords: Tourism; Ape Health; Apes